Normal-weight central obesity: implications for diabetes mellitus - Jin, Xueshan; Liu, Jiajun; Cao, Qiuyu; Lin, Jiehua; Wu, Guangfu; Liu, Longhui; Jiang, Shan; Zhou, Xin; Li, Zhiqiang; Yang, Aicheng (Frontiers in Nutrition, 2023)
Background: Current guidelines for obesity prevention and control focus on body mass index (BMI) and rarely address central obesity. Few studies have been conducted on the association between normal-weight central obesity and the risk of diabetes mellitus (DM). Methods: 26,825 participants from the National Health and Nutrition Examination Survey (NHANES) were included in our study. A weighted multivariate logistic regression model was used to analyze the relationship between different obesity patterns and the risk of DM. Results: Our results suggest that normal-weight central obesity is associated with an increased risk of DM (OR: 2.37, 95% CI: 1.75-3.23) compared with normal-weight participants without central obesity. When stratified by sex, men with normal-weight central obesity, obesity and central obesity were found to have a similar risk of DM (OR: 3.83, 95% CI: 2.10-5.97; OR: 4.20, 95% CI: 3.48-5.08, respectively) and a higher risk than all other types of obesity, including men who were overweight with no central obesity (OR: 1.21, 95% CI: 0.96-1.51) and obese with no central obesity (OR: 0.53, 95% CI: 0.30-0.91). Conclusions: Our results highlight the need for more attention in people with central obesity, even if they have a normal BMI.